2020
DOI: 10.1038/s41598-020-72901-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of the antischistosomal activity of curcumin loaded nanoparticles versus praziquantel in the treatment of Schistosoma mansoni

Abstract: Schistosomiasis is a serious parasitic infection affecting millions worldwide. This study aimed to explore the anti-schistosomal activity of curcumin and curcumin loaded gold-nanoparticles (Cur-GNPs) with or without praziquantel (PZQ). We used six groups of the C57BL/6 mice in which five groups were infected with Schistosoma Mansoni (S. mansoni) cercariae and exhibited, separately, to different treatment regimens of curcumin, curcumin loaded nanoparticle, and PZQ, in addition to one untreated group which acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The worm reduction rates of Cur and Cur-Nano were 40.06 & 62.19, respectively. This agreed with Mokbel et al (2020). Magalha-es et al (2009) reported that Cur treatment modulated humoral and cellular immune responses of Schistosoma mansoni-infected mice and led to a significant reduction of parasite burden and liver pathology.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The worm reduction rates of Cur and Cur-Nano were 40.06 & 62.19, respectively. This agreed with Mokbel et al (2020). Magalha-es et al (2009) reported that Cur treatment modulated humoral and cellular immune responses of Schistosoma mansoni-infected mice and led to a significant reduction of parasite burden and liver pathology.…”
Section: Discussionsupporting
confidence: 82%
“…Unfortunately, the therapeutic abilities of Cur are limited because of its poor solubility or stability in aqueous media and body flulow bioavailability (Tiwari et al, 2017). This was overcome by nanotization of Cur; which improved water solubility, bioavailability, plasma concentration, cellular permeability and enhances its activity against various microbial pathogens and parasites (Mokbel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…70 This in turn causes in situ lessening of the eggs’ ability to induce granulomata. Mokbel et al, 2020, 81 reported similar histopathological effects when testing the antischistosomal activity of curcumin-loaded nanoparticles, especially when combined with PZQ.…”
Section: Electron Microscope Studiesmentioning
confidence: 87%
“…In another study of combination drugs, Mokbel et al (2020) evaluated the use of curcumin‐loaded gold nanoparticles, a molecule present in the Curcuma longa plant, with or without praziquantel. Oral treatment of S. mansoni ‐infected mice using curcumin‐loaded gold nanoparticles combined with praziquantel caused a high reduction in worm burden (97.4%).…”
Section: Oral Drug Delivery System For the Treatment Of Ntdsmentioning
confidence: 99%